PERBEDAAN KEBIJAKAN HUTANG DARI SUDUT PANDANG MANAGERIAL OWNERSHIP DAN FREE AGENT - Puryandani, Siti (PRESTASI, 2011)
In a corporate have two aspect thatâs support corporate operational.There are manager or agent and shareholder. Manager have a part of corporate share is call managerial ownership and common manager or agent donât have corporate share. There are able to decide financial function like financing decision, investment decision and dividend decision.At financing decision, manager can be arange the capital structure of a corporate. The capital structure divide from internal funding and external funding. For example debt is a part of external funding. High or low debt can use by corporate consist with average debt to equity ratio (DER). If a average debt to equity ratio more than 1 it is mean grade of debt is high and this corporate in category risk taker. But If a average debt to equity ratio less than 1 it is mean grade of debt is low and this corporate in category risk avoider.This research to examine differently debt policy has taken by managerial ownership and free agent. Sampling adjustment by purposive sampling. Total sample is 128 corporate divide two sample. First it is corporate have a Â managerial ownership in corporate structure. Second sample it is corporate have a free agent in corporate structure. Hypothesis to execute with Mann Whiney test isÂ Z with threeÂ variabels are managerial ownership, free agent and debt policy. Finding research show no different between debt policy thatâs doing by managerial ownership and free agent. Managerial ownership and free agent have same perception and is category risk taker. This indicator of fact from average debt to equity ratio more than 1.Keywords: managerial ownership, free agent and debt policy.